Impact experiments on highly porous targets: Cavity morphology and disruption thresholds in the strength regime. (March 2015) - Okamoto, Takaya; Nakamura, Akiko M.; Hasegawa, Sunao
Abstract: Small bodies were probably very porous during the formation of the solar system. To understand the evolution of such bodies, impact experiments on sintered glass-bead targets with porosities of 80%, 87%, and 94% were performed at velocities of 1.8–7.2 km s −1 using various projectiles with densities ranging from 1.1 g cm −3 to 4.5 g cm −3 . Here we report on the resulting cavity morphologies formed by these impacts, with particular attention paid to the depth from the cavity׳s entrance hole to its maximum diameter, the entrance-hole diameter, and the maximum diameter. We obtained empirical relations of the entrance-hole diameter and the maximum diameter using non-dimensional parameters for crater scaling. We also report on the targets׳ disruption thresholds, Q ⁎ . Each Q ⁎ value is on the order of kilojoules per kilogram, which is higher than the equivalent values for pure ice targets and basalt targets determined from high-velocity impact experiments. Non-dimensional disruption thresholds, ρ t Q ⁎ / Y, where ρ t and Y are the targets׳ bulk densities and compressive strengths, respectively, are calculated for various targets including those used in this study; they are shown to be within approximately one order of magnitude for a given porosity, although the impact velocities and target sizes range from 1 m s −1 to 7.2 km s −1 and from 2 cm to 14 cm, respectively. The previous proposed strength parameter for the catastrophic disruption threshold, Π s ⁎, is also calculated. It is shown to be roughly constant, irrespective of porosity if we assume that the scaling parameter μ decreases linearly with increasing porosity. Highlights: Impact experiments on targets with porosity of 80%, 87% and 94% were conducted. Empirical relations of cavity dimensions are obtained. Disruption thresholds are compiled using non-dimensional parameters.